Strength and durability properties of cement bonded particleboard from leucaena leucocephala / Marzuki Ab. Rahman - Ab. Rahman, Marzuki (2009)
This study focuses on application of 8 and 16 year (8Y and 16Y) old of Leucaena leucocephala or locally known as petai belalang as wood particles in three and single-layered Cement Bonded Particleboard (CBP) and incinerator Waste Paper Sludge Ash (WPSA) from paper industry as a cement replacement in CBP manufacturing. The CBP panels in this study were made in three (3) layers (sandwiching board) and single (1) layer. The CBP specimens were prepared at six (6) series of wood to cement ratio for three-layered CBP and three (3) series wood to cement ratio for single-layered CBP. The effects of using different wood to cement ratio on the mechanical and physical properties of the resulted CBP boards were investigated. A combination of aluminum sulphate Al2 (SO4)3 and sodium silicate (Na2SiO3) were incorporated in the mixing system to improve the bonding properties between the binder and matrix. The mechanical and physical properties of the boards were evaluated based on Malaysian Standard MS 544: 2001. In three-layered CBP, three (3) different particle sizes of wood particles were adopted. Particle sizes which retained at 2 nun size were used to make a core layer while a combination of 1 mm and 0.5 mm particles in size was used for the outer layer. The study showed the strength properties of the boards satisfied the minimum requirement of Malaysian Standard and comparable to those of commercial CBP. The presence of higher proportions of WPSA as a part of Portland cement had reduced the mechanical properties and retarded the degree of cement hydration properties. The presence of WPSA up to 20% for 8Y CBP had generally met the Malaysian Standard requirement on mechanical properties. In terms of durability, the present CBP indicated that the CBP also resulted better mechanical and physical properties after being externally exposed to the Malaysian climate for up to 300 days.